Bioefficacy of imidacloprid 70 WG against sucking pests and effect on natural enemies in tomato ecosystem - Swami, Hemant; Ameta, O P; ., Lekha (Indian Journal of Plant Protection, 2020)
Field studies were carried out to evaluate the bioefficacy of imidacloprid 70 WG at 30, 40, and 50 g/ha (21, 28,and 35 g a.i./ha) along with imidacloprid 200 SL at 175 ml/ha and hiamethoxam 25 WG at 200 g/ha against thrips, whitefly and natural enemies in tomato ecosystem. Two sprays of imidacloprid 70 WG at 50 g/ha at 10 days interval caused highest reduction in the population of thrips, whitefly and realized higher marketable yield of tomato. Two sprays of imidacloprid 70 WG at 40 g/ha at 10 days interval was found at par with imidacloprid 70 WG at 50 g/ha in terms of mean per cent reduction in the population of whitefly and thrips and also the marketable yield of tomato. Spray of imidacloprid 70 WG at all the doses did not cause any adverse effect on common natural enemies in tomato ecosystem and even at higher doses, this insecticide did not produce any phototoxic symptom in tomato. The results revealed that neonicotinoids can be used in compatible manner in future IPM programmes for managing sucking pests and reducing adverse effect on natural enemies.